Swirl switching in spatially developing bent pipes - Lupi, Valerio; Massaro, Daniele; Peplinski, Adam; Schlatter, Philipp (Physical Review Fluids, 2025)
Swirl switching refers to the temporal rotation of the plane of symmetry of the cross-sectional vortices about the equatorial plane of the curved pipe and may induce significant vibrations in piping systems. The origin of this phenomenon is not yet understood, and its relationship with turbulent fluctuations in the upstream straight section is still debated in the literature. To assess the effect of upstream turbulence, direct numerical simulations are performed for spatially developing bent pipe flows under both laminar and turbulent inflow conditions. Additionally, the influence of the bending angle on swirl switching and time-averaged flow characteristics is investigated. Proper orthogonal decomposition (POD) is applied to three-dimensional velocity fields to extract spatially coherent structures responsible for swirl switching. The phenomenon is observed for both inlet velocity profiles and bending angles, although it does not correspond to the dominant mode in the case of laminar inflow conditions. A reduced-order reconstruction using the most energetically relevant antisymmetric POD modes indicates a link between swirl switching and the shear layer within the bend. We therefore infer that swirl switching could arise because of a symmetry-breaking shear layer instability, representing a stage in the bifurcation cascade that leads to turbulence.
CRIS-Team Scopus Importer:2025-12-19